Structural and Magnetic Properties of Ba3[Cu0.8−xZnxMn0.2]2Fe24O41 Z-Type Hexaferrites - Eman S. Al-Hwaitat; Sami H. Mahmood; Mahmoud Al–Hussein; Ibrahim Bsoul (Advances in Materials Science and Engineering)
We report on the synthesis and characterization of Ba3[Cu0.8−xZnxMn0.2]2Fe24O41 (x = 0.0, 0.2, 0.4, 0.6, and 0.8) barium hexaferrites. The samples were prepared by high-energy ball-milling technique and double-sintering approach. The effects of Zn substitution for Cu on the structural and magnetic properties of the prepared samples were investigated using X-ray diffraction (XRD), scanning electron microscopy (SEM), and vibrating sample magnetometer (VSM). XRD patterns of the samples revealed the presence of a major Z-type hexaferrite phase, together with secondary M-type and Y-type phases. The magnetic results indicated that the saturation magnetization increased slightly with increasing the Zn content, while the coercivity and magnetocrystalline anisotropy field exhibited a decreasing tendency with the increase of Zn content. The thermomagnetic curves revealed the complex magnetic structure of the prepared samples and confirmed that the Curie temperature of the magnetic phases decreased with increasing x as a result of the reduction of the strength of the superexchange interactions.